The Resurgence of Measles - A Tragic Residue of Covid Epoch - Mangala Belur; Kajal Srivastava; AKHILA B S; Hetal Rathod (Medsci Publications, 2023)
Measles is a highly contagious, serious viral disease mainly affecting children under the age of five with a case fatality rate ranging from 0.1% 1in developed world to as much as 30% among refugee communities. As of the beginning of November 2022, the most current monthly statistics submitted to the WHO indicated that India was one of the top 10 nations responsible for the highest number of cases (9500 cases) worldwide . The most significant factor was COVID pandemic that had detrimental impact on the main approach including nterruption of health services, supply-chain disruption and routine immunization-measles vaccination campaigns being paused or postponed in many countries to avert further spread of COVID-19 that lead to fall in consumption of MR vaccine in a span of few months after pandemic started. Other contributing factors might include burgeoning migrant community, missed doses of vaccination and malnutriton spike.There is a need  to urgently address the basic needs of health care facilities and to fill the gaps in routine immunization and its surveillance system to curb the measles outbreak in this post pandemic era.